The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s10922-019-09504-0
|View full text |Cite
|
Sign up to set email alerts
|

Resource Management in a Containerized Cloud: Status and Challenges

Abstract: Cloud computing heavily relies on virtualization, as with cloud computing virtual resources are typically leased to the consumer, for example as virtual machines. Efficient management of these virtual resources is of great importance, as it has a direct impact on both the scalability and the operational costs of the cloud environment. Recently, containers are gaining popularity as virtualization technology, due to the minimal overhead compared to traditional virtual machines and the offered portability. Tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 153 publications
0
14
0
Order By: Relevance
“…Finally, although designed for VMs, we consider that the ECO-VMAP model can also be used for allocating containers. Relatively recent container technology offers a lightweight alternative for virtual machines [58][59][60]. VMs are emulated by a hypervisor that runs on a physical server, i.e., host machine.…”
Section: The Eco-vmap Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, although designed for VMs, we consider that the ECO-VMAP model can also be used for allocating containers. Relatively recent container technology offers a lightweight alternative for virtual machines [58][59][60]. VMs are emulated by a hypervisor that runs on a physical server, i.e., host machine.…”
Section: The Eco-vmap Modelmentioning
confidence: 99%
“…Therefore, containers are considered to be more vulnerable to possible attacks from malicious containers and prone to higher security risks [63,64]. Although these risks can be reduced to a degree by using additional security mechanisms, these mechanisms would bring additional overhead reducing the performance and elasticity of container platforms [58,63]. Another important issue yet to be solved within container technology is migration [65].…”
Section: The Eco-vmap Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review by Maenhaut, Volckaert, Ongenae and De Turck [5] discusses challenges related to service orchestration, resource management and pricing in (distributed) clouds and the fog. An overview of the challenges in fog and edge computing is presented by Avasalcai, Murturi and Dustdar [6].…”
Section: Related Workmentioning
confidence: 99%
“…Some research has been done in related fields, see for example the studies reported in [17][18][19][20], but these have not been in the context of containers. Others have reviewed the use of containers from a general perspective, without special emphasis on scheduling of containerized edge computing, see for example studies in [21,22]. Ahmad et al [23] report a survey of scheduling techniques in edge computing.…”
Section: Introductionmentioning
confidence: 99%